Work centrality and recovery experiences in dual‐earner couples: Test of an actor‐partner interdependence model. (8th March 2022) - Hao, Leilei; Meng, Weixuan; Xu, Mengyang; Meng, Hui
Abstract: Work centrality refers to individual beliefs regarding the degree of importance that work plays in their lives. To date, very little is known about the relationship between employees' work centrality and their work recovery. According to the resource allocation theory and spillover‐crossover model, we aim to investigate the effects of work centrality on recovery experiences and explore the mediating role of spousal recovery support. Data from 177 matched dual‐earner couples ( N  = 354) in China were analysed using the actor‐partner interdependence model (APIM). Results showed that working couples who reported higher work centrality experienced lower levels of psychological detachment and relaxation. The wives' work centrality showed a direct and negative influence on the husbands' relaxation; however, no direct partner effects were found for husbands. Moreover, the wives' work centrality was related to the husbands' relaxation, mastery, and control experience through the husbands' perceived recovery support. Our results also suggested that the wives' perceived recovery support mediated the effects of the husbands' work centrality on the wives' psychological detachment, relaxation, mastery, and control experience when they had two children. Based on these findings, theoretical and practical implications are discussed.